2010
DOI: 10.1007/s00128-010-0087-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Combined Treatment of Landfill Urban Solid Waste Leachate and Sewage Using Danio rerio and Daphnia similis

Abstract: The co-treatment from Morro do Céu landfill leachate with domestic sewage in the Icaraí STP was monitored with regard to the behavior of toxicity of its inflows and outflow. Leachate not exceeded 1.5% in volume in the plant. The acute ecotoxicological tests showed that, although leachate is far more harmful to D. rerio (LC50 approximately = 4) and D. similis (LC50 approximately = 5) than sewage (LC50 approximately = 62; LC50 approximately = 22), statistically the mixture of leachate with sewage did not result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…This result is in agreement with Mannarino et al (2010) that showed values of 2-4 units of toxicity for 0.37 to 1.22% of landfill leachate in sewage (the same parameters used in this work).…”
Section: Third Step: Toxicity Testsupporting
confidence: 93%
See 4 more Smart Citations
“…This result is in agreement with Mannarino et al (2010) that showed values of 2-4 units of toxicity for 0.37 to 1.22% of landfill leachate in sewage (the same parameters used in this work).…”
Section: Third Step: Toxicity Testsupporting
confidence: 93%
“…The authors obtained the following value ranges: -for raw sewage, pH: 6.7 -7.6; Turbidity: 11.0 -328.4 NTU; COD: 53-316 mg.L -1 ; TSS: 100-250 mg.L -1 and N-NH 3 :11-70 mg.L -1 ; for landfill leachate, pH: 7.5-8.5; Turbidity: 2.0-70.5 NTU; COD: 685-1913 mg.L -1 ; TSS: 40-473 mg.L -1 and N-NH 3 :522-1394 mg.L -1. -Except for the pH of sewage and landfill leachate, which showed similar value ranges for both studies, the study from Mannarino (2010) shows greater variation than this study, probably because the sampling had been done during a year and so the samples showed a large range of variation. -Table 3 shows results of COD and Turbidity in the minimum conditions (coagulant and polyelectrolyte dosage) that achieved the minimum removal COD (30 %).…”
Section: First Step: Definition Of the Optimum Condition For Each Coamentioning
confidence: 47%
See 3 more Smart Citations